Avaliação de fontes e extratores de silício - Oliveira, Patrícia Ferreira de (2024)
Silicon (Si) is abundantly present in the earth's crust and is considered a beneficial element for plants, being absorbed in the form of monosilicic acid (H4SiO4). There are several products on the market that are marketed as silicon sources. However, it is necessary to investigate and identify those with the greatest potential in terms of cost, ease of application, soluble Si, Ca and Mg content. There are several extractors that evaluate the availability of Si in the soil, but their chemical characteristics can overestimate or underestimate the real content of the element present in the soil. The objectives of this study were to evaluate Si sources in terms of dry matter production and nutrient content in rice plants, and to assess the efficiency of Si extractors from the soil and their correlation with the dry matter of rice plants. The experiment was carried out in a greenhouse, in a completely randomized design, in a 10x5x5 factorial scheme, with ten soils, four treatments and the control without Si and five chemical extractants. The sources used were wollastonite, fluorite with silicon oxide, diopsite and diatomaceous earth, at a dose of 200 kg ha-1 of Si. The Si extractants evaluated were water, calcium chloride 0.01 mol dm- ³, acetic acid 0.5 mol dm-3, ammonium acetate 0.5 mol dm-3 + acetic acid 0.1 mol dm-3 and ammonium acetate 0.5 mol dm-3 + acetic acid 0.3 mol dm-3. The dry mass of the aerial part of the plants, the plant Si content, the Si accumulated by the plants, the Si extracted from the soils and the correlation between the Si present in the plant and the Si available in the soils for each extractant were evaluated. Dry mass production varied between treatments only in soils 2- PVAd, 9 - LVd and 10 - CXd. Plant Si content and accumulated Si were higher in the treatments with wollastonite and fluorite with silicon oxide. The amount of Si extracted by the extractants was higher with acetic acid and lower with water. The decreasing order of correlation was: ammonium acetate 0.5 mol dm-3 + acetic acid 0.3 mol dm-3 (R2 = 0.32) < calcium chloride (R2 = 0.27) < ammonium acetate 0.5 mol dm-3 + acetic acid 0.1 mol dm-3 (R² = 0.11) < acetic acid (R² = 0.10) < water (R² = 0.04).